Long-term consequences of early marriage and maternity in West and Central Africa: wealth, education, and fertility - Sagalova, Vera; Nanama, Simeon; Zagre, Noel Marie; Vollmer, Sebastian (Journal of global health, 2021)
Objective Early marriage and childbearing have substantial detrimental effects on both, the affected girls and women at the micro level, as well as entire economies on the macro level. West and Central African countries have some of the highest prevalence rates of early marriage and maternity worldwide. This work attempts to quantify the long-term economic, societal, and fertility effects of marriage and pregnancy in early and late adolescence in West and Central Africa. Methods We used pooled cross-sectional data collected between 1986 and 2017 in 21 West and Central African countries within the DHS and MICS programs to estimate the associations of marriage and maternity during early (10-14) and late (15-19) adolescence retrospectively on wealth accumulation, educational attainment, as well as the woman's lifetime fertility. Results Descriptively, women who married or gave birth as young or very young adolescents are overrepresented among the poorest and least educated quintiles of the adult population and underrepresented among the richest and most educated. These gradients were confirmed within a regression analysis which additionally controlled for current age of the woman and PSU fixed effects. Marrying in early/late adolescence was associated with a 12%/6% higher likelihood of being in the poorest wealth quintile in later life and 29%/20% increased likelihood of not completing primary education, as compared to women who married as adults. Maternity in early/late adolescence was associated with a 7%/4% higher likelihood of belonging to the poorest quintile and 17%/10% higher likelihood of being uneducated. Moreover, women who married/gave birth during early or late adolescence, on average, have 2.2/2.3 or 1.4/1.5 more children than those who have married/become mothers as adults. Conclusions Our findings suggest that the dire consequences of early marriage and maternity hit youngest girls the hardest - both immediately and long-term. Hence, it is not only worthwhile to prevent adolescent marriage and pregnancy in general, but also specifically target very young girls below age 15 to attempt to at least delay such far-reaching demographic life events.
Gesehen am 16.11.2021